Changes of protein oxidation, lipid oxidation and lipolysis in Chinese dry sausage with different sodium chloride curing salt content - Bing Zhao; Huimin Zhou; Shunliang Zhang; Xiaoqian Pan; Su Li; Ning Zhu; Qianrong Wu; Shouwei Wang; Xiaoling Qiao; Wenhua Chen (Food Science and Human Wellness)
The effect of sodium chloride (NaCl) curing salt content on protein oxidation, lipid oxidation and lipolysis of Chinese dry sausage was investigated. Two groups Chinese dry sausages with 2% and 4% (m/m) salt content were studied. The degree of protein oxidation increased during the processes in two groups sausages, while the content of phospholipids decreased, neutral lipids and free fatty acids increased. The degree of protein oxidation, lipid oxidation and lipolysis in 4% NaCl content group was higher than those in 2% NaCl content group, while 4% NaCl content group has higher lipase activity. In conclusion, 4% NaCl may facilitate the protein oxidation, lipid hydrolysis and oxidation in Chinese dry sausage, and the protein oxidation had strong correlation with lipid oxidation and lipolysis. The results could provide a basis for improving the technology of industrial production.